2013
DOI: 10.1103/physrevlett.110.176001
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Scale Simulation of Homopolymer Wall Slip

Abstract: The first molecular scale simulation of highly entangled polydisperse homopolymers that is capable of capturing all three regions--no slip, weak slip, and strong slip--of the hydrodynamic boundary condition is presented. An on-lattice dynamic Monte Carlo technique capable of correctly capturing both unentangled and entangled polymer dynamics is used to study the molecular details of wall slip phenomena for homopolymers and energetically neutral walls. For unentangled chains (those exhibiting Rouse dynamics) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…The implementation of polydispersity [33], shear flow [30], and parabolic flow [31] have been successfully demonstrated. In addition, the algorithm accurately captures polymer dynamics [30] and wall-slip phenomena [34].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The implementation of polydispersity [33], shear flow [30], and parabolic flow [31] have been successfully demonstrated. In addition, the algorithm accurately captures polymer dynamics [30] and wall-slip phenomena [34].…”
Section: Methodsmentioning
confidence: 99%
“…These simulations are at high shear rates and yet almost no additional migration other than that caused by the walls is evident. At even higher shear rates when slip and cohesive failure are present [34], additional migration can occur but this is accompanied by velocity banding, that is, by an inhomogeneous shear rate. The data of Figures 9 and 10 compared to that of Figs.…”
Section: B Segmental Distributionsmentioning
confidence: 95%
“…However, due to computational limitations, only the longer of the two chain lengths was well above the entanglement molecular weight M e . There have been few studies of polymer melts with a distribution of chains lengths, though mostly for short, unentangled polymers [19,23,[30][31][32][33][34][35][36][37]. Rorrer et al [19,[34][35][36] mapped a distribution of chain lengths on a small number of chain lengths and showed that for the same weight-averaged molecular weight, increasing the dispersity in chain lengths gives a lower Rouse time and introduces a broadening of the transition to reptation of the chains.…”
mentioning
confidence: 99%
“…As previously discussed, this is particularly useful for complex fluids which might exhibit layering or orientational ordering close to the boundaries. For example is known that polydisperse polymers, if confined, will distribute so as to have low molecular weight polymers collecting close to the boundaries [43]. Our study can therefore help the understanding and prediction of phenomena in small geometries and aid in the development of new nanodevices and lubricants.…”
Section: Introductionmentioning
confidence: 82%